2021
DOI: 10.3389/fphar.2021.728916
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Microarray Profiling Reveals hsa_circ_0058493 as a Novel Biomarker for Imatinib-Resistant CML

Abstract: Background: CircRNA has appeared as a critical molecular in the development of various cancers. However, the cellular function of circRNAs and exosomal circRNAs has not been well explored in Chronic myeloid leukemia (CML). Methods: Differentially expressed circRNAs were identified by a human circRNA microarray analysis. The expression of hsa_circ_0058493 in peripheral blood mononuclear cells (PBMCs) and exosomes was verified using quantitative real-time PCR. Short hairpin RNAs against hsa_circ_0058493 were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…To date, increasing literature demonstrates that circRNAs play a crucial role in the pathology of various diseases, including neuronal diseases ( Kumar et al, 2018 ; Dube et al, 2019 ), diabetes ( Liu et al, 2019 ) and cancer ( Guarnerio et al, 2016b ; Tang et al, 2021 ). Particularly, circRNAs serve important functions in hematological malignancies ( Bonizzato et al, 2016 ; Dahl et al, 2018 ), and our group also reveals that circRNAs can be a promising prognostic biomarker in hematological malignancies ( Zhong et al, 2021 ). Furthermore, circRNAs have also been found to be critically involved in cancer initiation, development and drug resistance ( Guarnerio et al, 2016a ; Borran et al, 2020 ).…”
Section: Introductionmentioning
confidence: 75%
“…To date, increasing literature demonstrates that circRNAs play a crucial role in the pathology of various diseases, including neuronal diseases ( Kumar et al, 2018 ; Dube et al, 2019 ), diabetes ( Liu et al, 2019 ) and cancer ( Guarnerio et al, 2016b ; Tang et al, 2021 ). Particularly, circRNAs serve important functions in hematological malignancies ( Bonizzato et al, 2016 ; Dahl et al, 2018 ), and our group also reveals that circRNAs can be a promising prognostic biomarker in hematological malignancies ( Zhong et al, 2021 ). Furthermore, circRNAs have also been found to be critically involved in cancer initiation, development and drug resistance ( Guarnerio et al, 2016a ; Borran et al, 2020 ).…”
Section: Introductionmentioning
confidence: 75%
“… Bi et al (2021) found that oncogene circ_0004136 could promote AML development through regulating miR-570-3p/TSPAN3 axis while exosome-mediated circ_0004136 knockdown restrained AML cell malignant progression. Our recent study also demonstrated that upregulated circ_0058493 in exosomes derived from CML cells was associated with imatinib resistance ( Zhong et al, 2021 ). Besides, Wu et al (2020) identified a novel mitochondrial genome-derived circRNAs (Mc), mc-COX2.…”
Section: Role Of Exosomal Circrnas In Leukemiamentioning
confidence: 88%
“… 40 Circ_0058493 was significantly overexpressed in PBMCs of CML patients with poor clinical response to imatinib. 41 Knockdown of circ_0058493 markedly repressed the growth of imatinib‐resistant CML cells probably via acting as a molecular sponge to miR‐548b‐3p, suggesting that circ_0058493 in PBMCs might be a useful prognostic biomarker as well as a therapeutic target for CML. 41 CircHIPK3 was also significantly elevated in PBMCs and the serum in CML patients with poor outcomes.…”
Section: Circrnas and Leukemiamentioning
confidence: 97%